“MISSA ZANDE”, by Fr. F. GIORGETTI, F.S.C. Discoteca Comboniana, Editrice Nigrizia, via Meloncello 3/3, Bologna, Italy. Recorded by the choir of Missione Africane di Rebbio, directed by P. S. Benedetti and (drums) Prof. Bionda Lonello. 7-inch L.P. “MISA BABA YETU” (Mass “Our Father”) by STEPHEN MBUNGA. Mnsica Verba, available at the Benedictine Seminary of Peramiho, Tanzania, where it was recorded. 7-inch L.P. - Basil, Brother (International Library of African Music, 1964)
pages: 122-123
Keywords: African Music; Tanzania